Sex Differences in Episodic Memory Variance - Asperholm, Martin; van Leuven, Livia; Herlitz, Agneta (Frontiers in Psychology, 2020)
Men as a group have been shown to have larger variances than women in several areas pertaining to both biological and psychological traits, but no investigation has been performed in regard to episodic memory. We conducted an analysis on sex differences in episodic memory variance on 535 studies, representing 962,946 individuals, conducted between 1973 and 2013. Results showed that men had larger variances than women in verbal episodic memory tasks as well as episodic memory tasks having to do with spatial locations. Women, on the other hand, had larger variance than men for tasks involving remembering routes. These effects were for the most part small, and exploratory analyses suggest that they might come about, at least in part, because of measures not sufficiently controlled for ceiling effects. This means that the effects should be interpreted with caution and that further research on sex differences in episodic memory variance is needed.